Use of subclavian steal in treating chronic total subclavian artery occlusion. (October 2013) - Goel, Pravin K; Moorthy, Nagaraja
Endovascular treatment is a well-established option for subclavian artery stenosis. However, total occlusion of the proximal subclavian artery remains a challenge, posing difficulties of nonvisualization of distal vessels, access site issues, and deployment of vertebral embolism protection devices. A 65-year-old man with chronic total occlusion of the ostial left subclavian artery, underwent successful endovascular stenting in which the subclavian steal phenomenon was utilized as a roadmap to cross the occlusion.